Circadian Variation of Sleep During the Follicular and Luteal Phases of the Menstrual Cycle - Shechter, Ari (Associated Professional Sleep Societies, LLC, 2010)
STUDY OBJECTIVES: Women experience insomnia more frequently than men. Menstrual cycle changes in reproductive hormones and circadian rhythms may contribute to sleep disruptions. Our aim, therefore, was to clarify the interaction between menstrual and circadian processes as it affects sleep. DESIGN: Participants entered the laboratory during the mid-follicular (MF) and mid-luteal (ML) phases of their menstrual cycle for an ultra-rapid sleep-wake cycle (URSW) procedure, consisting of 36 cycles of 60-min wake episodes alternating with 60-min nap opportunities. This procedure concluded with an ad libitum nap episode. SETTING: Time-isolation suite. PARTICIPANTS: Eight unmedicated, physically and mentally healthy females with regular ovulatory menstrual cycles. INTERVENTIONS: N/A MEASUREMENTS: Polysomnographic sleep from nocturnal sleep episodes and 60-min naps; subjective alertness; core body temperature (CBT); salivary melatonin; urinary estradiol; and urinary progesterone. RESULTS: Increased CBT values at night and decreased CBT amplitude were observed during ML compared to MF. Circadian phase of CBT and the circadian melatonin profile were unaffected by menstrual phase. All analyzed sleep parameters showed a circadian variation throughout the URSW procedure, with no menstrual phase differences observed for most, including slow wave sleep (SWS). The circadian variation of REM sleep duration, however, was sensitive to menstrual phase, with reduced REM sleep during ML at circadian phase 0° and 30°. CONCLUSIONS: Moderate but significant changes in REM sleep across the menstrual and circadian cycles were observed. These results support an interaction between circadian and menstrual processes in the regulation of REM sleep. CITATION: Shechter A; Varin F; Boivin DB. Circadian variation of sleep during the follicular and luteal phases of the menstrual cycle. SLEEP 2010;33(5):647-656.